Novel Optical Fibers for High-Capacity Transmission System - Mingjun Li; Hao Chen (Dianxin kexue, 2014)
Novel optical fibers for increasing capacity for transmission system was discussed.For conventional fibers for long haul transmission,because transmission impairments such as chromatic dispersion,polarization-mode dispersion can be perfectly compensated for by digital signal processing,the only fiber parameters that can be optimized further are fiber attenuation and effective area.System figure of merit for the two parameters was discussed and recent results on ultra-low loss and large effective area fibers were presented.For short reach applications,the current efforts in improving multimode fiber bandwidth were reviewed and new trends in multimode fibers to meet future bandwidth demand were discussed.For next generation fibers,multicore and few mode fibers for space division multiplexing would be focused on,which has the potential to increase the capacity by an order of magnitude.Fiber design considerations were presented and recent progress on multicore and few mode fibers was reviewed.Finally,major challenges in space division multiplexing applications using multicore and few mode fibers were discussed.